2017
DOI: 10.18632/oncotarget.15413
|View full text |Cite
|
Sign up to set email alerts
|

Diosmetin exerts anti-oxidative, anti-inflammatory and anti-apoptotic effects to protect against endotoxin-induced acute hepatic failure in mice

Abstract: To investigate the effects and mechanism of diosmetin on acute hepatic failure (AHF), an AHF murine model was established through administration of lipopolysaccharides/D-galactosamine (LPS/D-GalN). In vitro, diosmetin scavenged free radicals. In vivo, diosmetin decreased mortality among mice, blocked the development of histopathological changes and hepatic damage, and suppressed levels of inflammatory mediators and cytokines. In addition, diosmetin prevented the expression of phosphorylated IKK, IκBα, and NF-κ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 37 publications
3
48
0
Order By: Relevance
“…The hepatoprotective phytoconstituents of CH might include flavonoids, such as silibinin diastereomers and phenylethanoid glycosides, because the hepatoprotective ingredients of C. japonicum are flavonoids and the hepatoprotective ingredients of C. setosum are phenylethanoid glycosides [ 11 , 12 ]. The efficacy of CJF, which showed the best hepatoprotective effects among the four Cirsium species, might be due to silibinin diastereomers and diosmetin because diosmetin could inhibit CYP 2E1 [ 38 ] and it possesses antioxidant and anti-inflammatory activities against endotoxin-induced acute liver injury [ 39 ]. Therefore, the hepatoprotective phytoconstituents of CH against CCl 4 -induced acute liver damage must be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatoprotective phytoconstituents of CH might include flavonoids, such as silibinin diastereomers and phenylethanoid glycosides, because the hepatoprotective ingredients of C. japonicum are flavonoids and the hepatoprotective ingredients of C. setosum are phenylethanoid glycosides [ 11 , 12 ]. The efficacy of CJF, which showed the best hepatoprotective effects among the four Cirsium species, might be due to silibinin diastereomers and diosmetin because diosmetin could inhibit CYP 2E1 [ 38 ] and it possesses antioxidant and anti-inflammatory activities against endotoxin-induced acute liver injury [ 39 ]. Therefore, the hepatoprotective phytoconstituents of CH against CCl 4 -induced acute liver damage must be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The median survival is generally less than 1 year from the time of diagnosis, and even under the most favorable situations, most patients die within 2 years [7]. Diosmetin has been previously demonstrated to induce cell apoptosis and act as an anticancer compound in several cancers [23][24][25][26]. However, the effects of diosmetin on glioma have not been elucidated, and whether diosmetin can affect glioma development and the underlying mechanisms remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The anti‐inflammatory effect of diosmetin was mediated by the Akt/NF‐κB/iNOS signaling pathway (Jiang, Liu, Zhou, Liu, & Liu, ). Diosmetin suppressed LPS/D‐galactosamine (D‐GalN)‐induced production of inflammatory mediators and cytokines, for example, iNOS, prostaglandin E2, cyclooxygenase‐2, TNF‐α, IL‐1β, and IL‐6, which was regulated by NF‐κB and mitogen‐associated protein kinases (MAPKs) signaling pathways (Yang et al, ). Chandler et al reported that diosmetin inhibited advanced glycation endproducts (AGEs)‐induced production of NO and TNF‐α in N‐11 murine microglia (Chandler et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Diosmetin (Figure ), a bioflavonoid that is abundant in citrus fruits, has been found to possess broad activities, for example, anti‐inflammatory, anti‐oxidant, anti‐apoptotic, anti‐tumor, and anti‐virulence activities (Liu et al, ; Oak et al, ; Yang et al, ). It has been proven that diosmetin protects mice from endotoxin‐induced acute hepatic failure through its anti‐oxidant and anti‐inflammatory effects (Yang et al, ). Diosmetin relieves LPS‐induced acute lung injury via suppressing inflammatory cell infiltration and proinflammatory cytokines overproduction in bronchoalveolar lavage fluid (Liu, Ci, Wen, & Peng, ).…”
Section: Introductionmentioning
confidence: 99%